THE EFFECT OF WORK DISCIPLINE AND WORKLOAD ON SUSTAINABLE EMPLOYEE PERFORMANCE AT PT. KIANJAYA MACHINERY, BANDUNG - Dea Puteri Auliasari; Hadi Ahmad Sukardi; Ahmad Zulfahmi Ubaidillah; Agrie Wahyudi Kharisman (PT. Altin Riset Publishing, 2026)
This study aims to analyze the effect of work discipline and workload on employee performance at PT. Kianjaya Machinery in Bandung City. The background of this study is based on significant fluctuations in employee absenteeism rates (peaking above 40% in April 2024) and the instability of the company's sales throughout 2024, which indicate problems with employee performance. The pre-survey showed that 62.23% of employees felt that their performance was not optimal, 60% showed a lack of work discipline (being late and postponing tasks), and 60% felt a high workload, both mentally and physically. Therefore, this study was conducted to describe the conditions of work discipline, workload, and employee performance, and to measure how much influence work discipline and workload, both partially and simultaneously, have on employee performance at PT. Kianjaya Machinery. The research method used is descriptive and verification analysis with a quantitative approach. Data were collected through questionnaires distributed to 42 employees of PT. Kianjaya Machinery. Data analysis techniques include multiple linear regression, correlation coefficient analysis, and determination coefficient analysis using IBM SPSS. The research findings show that work discipline and workload positively and significantly affect employee performance. The regression equation obtained is Y = 1.091 + 0.254 (X1) + 0.378 (X2). The relationship between work discipline and employee performance is classified as